Food absence is a cue for metamorphosis in the solitary bee Megachile rotundata through a conserved physiological mechanism - Courtney C. Grula; Jeffrey D. Kittilson; Jason Holthusen; Joseph P. Rinehart; Julia H. Bowsher (Proceedings of the National Academy of Sciences, 2026)
The timing of metamorphosis in insects determines adult body size and influences aspects of fitness including flight performance and fecundity. The regulation of metamorphosis has been well studied in model insects but determining the cue that initiates the physiological shift toward metamorphosis in other insects has been challenging. In most insects, the critical weight is a cue to initiate metamorphosis. Our goal was to determine the cue for metamorphosis in the solitary bee Megachile rotundata and to characterize the physiological mechanisms initiated by this cue. Larval bees were fed ad libitum (also termed “fed”) or had all food removed (also termed “starved”). We measured the time to initiate metamorphosis, juvenile hormone (JH) titers, and the abundance of transcripts involved in the endocrine response to metamorphosis. We experimentally manipulated JH by topically applying precocene, which interrupts JH production. We found that M. rotundata does not have a critical weight and that starvation through the removal of food triggered the initiation of metamorphosis. Food removal was associated with low JH titers, and the application of precocene mimicked the response to food absence. Food removal decreased transcripts associated with JH production, and increased transcripts involved in ecdysone synthesis and insulin/TOR signaling. Food absence is an ecologically relevant cue for a M. rotundata larva, which is provisioned a finite amount of food and is unable to forage for additional food. Despite having food removal as a cue for metamorphosis, the physiological mechanisms associated with metamorphosis are similar to those found in other insects.